THE DEVELOPMENT OF BRAILLE PUZZLE MEDIA FOR INCREASING THE ABILITY OF READING AND WRITING FOR CHILDREN WITH VISUAL IMPAIRMENT OF 4TH GRADE IN THE ELEMENTARY SPECIAL EDUCATION - Styaputra, Fahrizal Oktova Anggara (JPI (Jurnal Pendidikan Inklusi), 2017)
The Development of Braille Puzzle Media for Increasing The Ability of Reading and Writing for Children With Visual Impairment of 4th Grade In Elementary Special Education. The purpose of this research is developping a media that can be used to increase the reading and writing ability of child with visual impairment on fourth grade in elementary special education. This research was adapted by steps of Sugiyonos model consisting of eight steps. The result of media experts 88% , matter experts 90%, practicy experts 82%, small group testing 82%. So this product braille puzzle otherwise very worthy to be used